3
2007-01-14 12:29:22
·
answer #1
·
answered by zephrrrrrrrrrrr 2
·
0⤊
2⤋
3
2007-01-14 12:33:05
·
answer #2
·
answered by Dink 1
·
0⤊
0⤋
3
2007-01-14 12:31:09
·
answer #3
·
answered by WxEtte 5
·
0⤊
0⤋
+3
2007-01-14 12:29:58
·
answer #4
·
answered by hasgr8boyz 3
·
0⤊
0⤋
4-6+5=3
2007-01-14 12:31:51
·
answer #5
·
answered by lulu 3
·
0⤊
0⤋
If x=2
then x^2 = 4
-3x = -6
combining
4-6+5 = 3
2007-01-14 12:30:40
·
answer #6
·
answered by ignoramus 7
·
0⤊
0⤋
(2)2 - 3(2) + 5
(4 - 6 )+ 5
-2 + 5 = 3
2007-01-14 12:30:57
·
answer #7
·
answered by curiosityreincarnated 3
·
0⤊
0⤋
4-6+5=3 :)
2007-01-14 12:29:57
·
answer #8
·
answered by =] 3
·
0⤊
0⤋
D in basic terms calculate G(4) meaning plug in 4 for x: g(x)=3x+2 g(4)= 3(4)+2 =14 pondering g(4)=14, you may plug that for the dimensions of and calculate f(14) = x^2-5x+4 (14)^2-5(a4)+4 =196-70+4 = a hundred thirty so your answer is D stable success
2016-12-16 04:49:53
·
answer #9
·
answered by ? 4
·
0⤊
0⤋
Assuming that is an exponent:
2^2 - 3(2) + 5 = 4 - 6 + 5 = 3
2007-01-14 12:29:35
·
answer #10
·
answered by keely_66 3
·
0⤊
2⤋